A study on the relationship between leadership style and employee motivation at Tangkak District Council / Nur Ainina Mohd Yusof - Mohd Yusof, Nur Ainina (2015)
This study is to determine the relationship between transactional leadership, transformational leadership and employee motivation among staff at Tangkak District Council. A quantitative approach and descriptive research design was use in this study. Two hypotheses were proposed to test the relationship between transactional leadership, transformational leadership and employee motivation at Tangkak District Council. The research instrument was structured by questionnaire. All staff at Tangkak District Council was been selected for this study. For this study, only 118 of staff that been selected for the sample. This study use convenience sampling technique to select the sample for this study. Besides that, multiple regression analysis, correlation, frequency and descriptive statistic were used to determine the relationship between transactional leadership, transformational and employee motivation. Based on this study, there is a relationship between leadership style which is transactional leadership style and transformational leadership style with employee motivation. Refer on finding, the transactional leadership style has a moderate relationship with employee motivation while the transformational leadership style has weak relationship with employee motivation.